26x+3=5(5x+8)

Simple and best practice solution for 26x+3=5(5x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 26x+3=5(5x+8) equation:


Simplifying
26x + 3 = 5(5x + 8)

Reorder the terms:
3 + 26x = 5(5x + 8)

Reorder the terms:
3 + 26x = 5(8 + 5x)
3 + 26x = (8 * 5 + 5x * 5)
3 + 26x = (40 + 25x)

Solving
3 + 26x = 40 + 25x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-25x' to each side of the equation.
3 + 26x + -25x = 40 + 25x + -25x

Combine like terms: 26x + -25x = 1x
3 + 1x = 40 + 25x + -25x

Combine like terms: 25x + -25x = 0
3 + 1x = 40 + 0
3 + 1x = 40

Add '-3' to each side of the equation.
3 + -3 + 1x = 40 + -3

Combine like terms: 3 + -3 = 0
0 + 1x = 40 + -3
1x = 40 + -3

Combine like terms: 40 + -3 = 37
1x = 37

Divide each side by '1'.
x = 37

Simplifying
x = 37

See similar equations:

| 56=-2(21-m)+4(m-4) | | -17=x-36 | | T=0.6(205-18/2-144)+144 | | 0.40=ln(y) | | 6(4x-7)-4=6(x-4)+104 | | 3x-2-5x=x+2+x | | 16p^4-4p^2=0 | | 6/5+2/5x=29/10+5/2x+1/2 | | 9x-8x=19fory | | 2(x-5)+10=-(-3x+2) | | 5(3x-7)-8=5(x-3)+22 | | 11y+15x=-23 | | 7x+n=5 | | 10=11x | | 5(-7x-5)-4x=2 | | (7c-5)(8c+4)= | | 2(10x-5)-9x=11x+13 | | 4+(10+10)+x=30 | | 5/18=-y/6 | | x+9.3=8 | | n+2=-14-4 | | -7/8t=1/4 | | 7k+2=4x-10 | | 1/5m=9/5 | | -7.6=u/4-1.2 | | 0.20(x+30)+0.20x=10 | | e^7x=3 | | 3/5x+5=7 | | 6/5=2x | | 0.20(x+30)+0.20x= | | x/3=x/4-3 | | (1/x-2)+(x/x+2)=(5/x^2-4) |

Equations solver categories